OPERATIONAL INFORMATION SYSTEM DESIGN AT SIGAR JAYA FOTOCOPY - Joosten, Joosten; Hita, Hita (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
UMKM Sigar Jaya Fotocopy is one of the services in the form of photocopying which was founded in 2020 until now located in the Medan Sunggal sub-district area. Sigar Jaya Fotocopy not only serves photocopies but can print documents and photos and sell other office stationery. In the sales process, the owner needs help handling sales data recap, and in the purchasing process, the owner needs help checking the selling price of goods in large quantities. In the inventory process, the owner still uses manual checking where there can be a discrepancy in the available inventory. The System Development Life Cycle (SDLC) is the Information System Design method. The input design uses Visual Studio 2015